Management of Rectification of the Consequences of an Emergency Situation - Klimentevich Chernykh, Andrey; Arkadyevich Nefedyev, Sergey; Nikolaevich Bardulin, Evgenij; Pavlovich Andreev, Vladislav; Vladimirovna Stashevskaya, Olga (International Journal of Engineering and Technology, 2018)
The purpose of the paper is to develop an information technology used to implement operational and quality management of rectification of the consequences of an emergency situation. Typical examples are given of malicious programs and the ways of their impact on the work of computers used to develop solutions for the elimination of the consequences of an emergency situation. To prevent unauthorized access to computers and their infection with malicious programs, preventive measures are recommended. The novelty of the paper is the development of an information technology to recover the encrypted or blocked by malicious programs data necessary to develop solutions for the elimination of the consequences of an emergency situation and the concept of building a fragment of an information system within which this information technology should be implemented. The authors consider an approach to the improvement of the information system for officials of the management bodies of the Ministry of Emergency Situations of Russia, developing a solution for the relief of the consequences of an emergency situation, which provides the protection of their personal computers from malicious programs.Â Â